Repeat thrombolysis or conservative therapy vs. rescue percutaneous coronary intervention for failed thrombolysis: systematic review and meta-analysis. - Testa, L; van Gaal, W; Biondi-Zoccai, G; Abbate, A; Agostoni, P; Bhindi, R; Banning, A (2008)
BACKGROUND: Despite proven advantages of primary percutaneous coronary intervention (PCI), thrombolysis remains the first line treatment for ST-elevation myocardial infarction (STEMI) worldwide. Management of patients with failed thrombolysis is still debated, and data from existing randomized controlled trials are conflicting. AIM: To compare the risk/benefit profile of repeat thrombolysis (RT) vs. rescue PCI in patients with failed thrombolysis. METHODS: Search of BioMedCentral, CENTRAL, mRCT and PubMed for randomized controlled trials comparing rescue PCI vs. conservative therapy and/or RT vs. conservative therapy. Outcomes of interest assessed by adjusted indirect meta-analysis: major adverse events (MAE, defined as the composite of overall mortality and re-infarction), stroke, congestive heart failure (CHF), major bleeds (MB), and minor bleeds. Overall mortality and re-infarction have been also analysed individually. RESULTS: Eight trials were included (1318 patients). Follow-up ranged from 'in-hospital' to 6 months. No significant difference was found for the risk of MAE [OR 0.93(0.26-3.35), P = 0.4], overall mortality [OR 1.01(0.52-1.95), P = 0.15], stroke [OR 5.03(0.64-39.1), P = 0.58] and CHF [OR 0.74(0.28-1.96), P = 0.6]. Compared with conservative therapy, rescue PCI was associated with a 70% reduction in the risk of re-infarction [OR 0.32(0.14-0.74), P = 0.008], number needed to treat 17. No difference in terms of MB was found [OR 0.5(0.1-2.5), P = 0.09], while a greater risk of minor bleeds was observed with rescue PCI [OR 2.48(1.08-5.7), P = 0.04], number needed to harm 50. CONCLUSION: Although the observed benefit is modest, these data support the use of PCI after failed thrombolysis.